PENCEGAHAN PENULARAN COVID-19 DALAM KELUARGA DI PERUMAHAN TAMPAN PERMAI PANAM PEKANBARU - Denai Wahyuni; Henny Maria Ulfa; Risa Amalia; Wulan Sari (Panrita Abdi - Jurnal Pengabdian pada Masyarakat, 2022)
Basically, this community service activity focuses on providing knowledge to the community about preventing the transmission of COVID-19 in the family. The activity was in the form of education about health programs through counseling, which was attended by 20 people. The method of counseling is in the form of lectures and direct demonstrations face-to-face. Participants who participated in this activity focused only on PKK women in Tampan Permai Panam Housing. Educational materials for the introduction of COVID-19, communication within the family, the first action to prevent family clusters, protection and application of health protocols in the family and consuming nutritious food to increase body immunity. The media used are videos, posters and brochures. The knowledge assessment process is carried out by pretest and post-test in pre and post extension activities. The results of the pre test showed that the average knowledge was low (50.5%), moderate (30.8%) and high (18.3%). Meanwhile, the post-test results showed a significant increase. Knowledge is low (8.3%), medium (15%) and high (75.8%). This health education program through counseling is considered effective as a preventive measure for the transmission of COVID-19 in the family. — Pada dasarnya kegiatan pengabdian masyarakat ini berfokus untuk memberikan pengetahuan kepada masyarakat mengenai pencegahan penularan COVID-19 di dalam keluarga. Kegiatan berupa edukasi tentang program kesehatan melalui penyuluhan, yang dihadiri 20 orang. Metoda penyuluhan berupa ceramah dan demontrasi secara langsung dengan tatap muka. Peserta yang berpartisipasi dalam kegiatan ini berfokus hanya pada ibu- ibu PKK di Perumahan Tampan Permai Panam. Materi edukasi pengenalan COVID-19, komunikasi di dalam keluarga, tindakan pertama pencegahan klaster keluarga, perlindungan dan penerapan protocol kesehatan di dalam keluarga serta mengkonsumsi makanan yang bergizi meningkatkan imunitas tubuh. Media yang digunakan berupa video, poster dan brosur. Proses penilaian pengetahuan dilakukan dengan pretest dan post-test pada pra dan pasca aktivitas penyuluhan. Hasil pre test menunjukkan bahwa rata-rata pengetahuan rendah (50,5%), sedang (30,8 %) dan tinggi (18,3 %). Sedangkan hasil post-test terjadi peningkatan yang signifikan. Pengetahuan rendah (8,3%), sedang (15%) dan tinggi (75,8%). Program edukasi kesehatan melalui penyuluhan ini dinilai efektif sebagai tindakan preventif penularan COVID-19 di dalam keluarga.